Service Logistics and Workflow Optimization in the Radiology Department: A CT-Scan Case Study at PKU Muhammadiyah Hospital, Indonesia - Ruliyandari, Rochana; Tukiyo, Intan Wahyuni; Andrianty, Athika Ayu; Kuncara, Evrin Isna Nur; Kusumawati, Renita (Universitas Muhammadiyah Yogyakarta, 2026)
This research examined service logistics and workflow efficiency in the CT-Scan department at PKU Muhammadiyah Hospital, Yogyakarta. As demand for diagnostic imaging increases, this study aimed to describe the distribution of CT examinations by examination type, gender, and age group, and to map workflow patterns within the radiology service process. This study used a retrospective descriptive design to analyze CT scan records of 110 patients in April 2025. Simple Head CT scans represented 75.4% of exams, mostly for neurological disorders. Male patients accounted for 50.9% of the population, and 30% were aged 66–75. These statistics describe the radiology department's patient distribution and CT service use during the research. These findings may provide foundational data for the planning of radiology service capacity and resource distribution. Further research is required to assess operational performance metrics and workflow efficiency in radiology services across various hospital environments.